The Stability and Growth Pact three decades later - Hukkinen Juhana; Viren Matti (SUERF - The European Money and Finance Forum, 2026)
After 30 years of life with the Stability and Growth pact, it is surely worth asking whether the basic elements of the treaty still make sense and whether the proposed changes in the treaty would make a difference. We show that the deficit criterion is based on overly optimistic assumptions on economic growth that lowers debt ratios. If economic growth settles down to current rates, a much more stringent deficit level is required. Hence, attempts to allow more flexibility to this criterion will also be counterproductive.After 30 years of life with the Stability and Growth pact, it is surely worth asking whether the basic elements of the treaty still make sense and whether the proposed changes in the treaty would make a difference. We show that the deficit criterion is based on overly optimistic assumptions on economic growth that lowers debt ratios. If economic growth settles down to current rates, a much more stringent deficit level is required. Hence, attempts to allow more flexibility to this criterion will also be counterproductive.